Aspectos neuropsiquiátricos da depressão na epilepsia do lobo temporal - Guilherme Nogueira Mendes de Oliveira (2011)
Psychiatric and behavioral changes are commonly described in the epileptic syndromes, especially on those in which seizures arise from temporal lobes. Temporal lobe epilepsy (TLE) is responsible for most cases of epilepsy in adults and the complex interface between temporal structures and psychiatric disorders has been discussed in theliterature. The main objective of this study was to evaluate the neuropsychiatric and behavioral changes related to depression in TLE. We used structured clinical interview (MINI-PLUS), as well as tools for assessment of psychiatric symptoms, depression screening and assessment of psychopathological disorders not usually contemplated by traditional psychiatric classifications. A high frequency of mental disorders was identified, especially anxiety and mood disorders. Lifetime depression was diagnosed in about 40% of individuals with TLE and more than one quarter of patients were depressed at assessment. Depression was undertreated in more than 90% of cases. Wefound that treatment of depression is of great relevance, since it is the main factor related to suicide risk, even when considering clinical variables and impulsivity. From this observation, we analyzed the main instruments to assess depressive symptoms in this population. We proposed a cutoff at 16 (> 16) for both the Beck DepressionInventory (BDI) and Hamilton Rating Scale for Depression (HAM-D), instruments routinely used in clinical practice for depression diagnosis in epilepsy. In addition, we translated and validated for Brazilian population an instrument specifically developed for the screening of depression in epilepsy, the Neurological Disorders Depression Inventory for Epilepsy (NDDI-E). Complementing the neuropsychiatric assessmentfrom a multidimensional perspective, we translated and adapted to the Brazilian context the Interictal Dysphoric Disorder Inventory (IDDI) and the Neurobehavior Inventory (NBI). NBI evaluation in TLE showed an important influence of depression in behavioral traits, such as emotionality and viscosity, reinforcing the relevance of depression assessment in the study of behavior in TLE. A more accurate recognition of psychiatric comorbidity in TLE can help in understanding the role of the temporal lobes in mental disorders and behavior, as well as the development of strategies to propitiate the correct diagnosis and treatment of these disorders.